Pendampingan Legalitas dan Pemasaran pada UMKM “Bakso Kalsium” di Desa Sumberjo Kecamatan Rembang Kabupaten Rembang - Avivah Inaroh Nahdhiyah; Lu’lu’ Luthfiana; Siti Alliyah (Sekolah Tinggi Ilmu Ekonomi Surakarta, 2023)
Business work lecture activities (KKU) aim to facilitate and develop UMKM so that they become more modern businesses with the times. The UMKM facilitated by the authors are the UMKM Bakso Kalsium located on Jl. Slamet Riyadi No. 27 Karangmencol Kel. Sumberjo Kec. Rembang Regency Rembang. In the implementation of KKU in UMKM Bakso Kalsium the KKU Team provided assistance with predetermined programs including; (1) Renewal of product labels or stickers; (2) registration of business addresses on Google Maps; (3) Simple financial bookkeeping; (4) Making business nameplates; (5) Making online marketing media in the form of Facebook; (6) Making NIB business licenses online and; (7) Making NPWP. The results of implementing UMKM have new product stickers, UMKM business addresses have been registered on GoogleMaps, simple financial bookkeeping, business nameplates attached as business identity, online marketing media in the form of Facebook, business license certificates in the form of NIB (Business Identification Number). and have a NPWP that can be useful for UMKM owners.